A new species of the genus Omaliopsis Jeannel, 1940 (Coleoptera: Staphylinidae: Omaliinae: Omaliini) from northern Sichuan, China - Shavrin, Alexey V. (Zootaxa, 2020)
The omaliine genus Omaliopsis Jeannel, 1940 includes twelve species distributed in the Ethiopian, Madagascan, Palaearctic and Nearctic regions (Herman 2001, Shavrin 2019). The present paper is a supplement to my previous study (Shavrin 2019) and presents an additional description of a new species from the northern Sichuan, China.